Analisis Strategi Pemasaran Produk Fashion dalam Meningkatkan Pendapatan Pedagang Fashion di Era Persaingan Digital Perspektif Bisnis Islam Studi Kasus Pasar Tradisional Modern (PTM) - Nurul Aini; Eka Sri Wahyuni; Badaruddin Nurhab (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
ModernTraditional Market (PTM) of Bengkulu City based on the 4P concept (Product, Price, Place, Promotion) and the STP approach (Segmentation, Targeting, Positioning) in an effort to increase income and compete in the digital era. In addition, this study also explores the application of Islamic values ​​​​in the marketing strategies applied. To test this, researchers used qualitative methods with data collection techniques through in-depth interviews, observations, and documentation studies. From the results of the study, the results of the study indicate that the 4P-based marketing strategy (Product, Price, Place, Promotion) is well implemented by traders in PTM Bengkulu City. Traders are able to adjust products to developing trends, set flexible prices, rely on physical stores for distribution, and carry out traditional promotions. Meanwhile, in the application of STP (Segmentation, Targeting, Positioning), traders apply segmentation based on demographics and shopping behavior, targeting certain segments such as teenagers and the lower middle class, and positioning quality products that are relevant to trends but remain affordable. Islamic values ​​including shiddiq (honest), amanah (trustworthy), tabligh (transparently conveying information), and fathanah (intelligent) are also applied by traders in their marketing strategies. The application of these values ​​helps build consumer trust and maintain good long-term relationships. Thus, this marketing strategy not only helps traders in facing digital competition, but also creates consumer integrity and loyalty.